Microvascular Flaps in Nasal Reconstruction - Kim, Irene A.; Boahene, Kofi D. O.; Byrne, Patrick J.; Desai, Shaun C. (Facial Plastic Surgery, 2017)
Nasal reconstruction for subtotal and total rhinectomy defects is a challenging endeavor, which requires technical finesse, a keen artistic eye, and the ability to anticipate long-term changes that accompany postoperative healing. While local and regional flaps have traditionally been utilized to reconstitute missing nasal elements, certain situations may not provide sufficient or acceptable tissue for optimal reconstruction. In these situations, the three major components of the nose—lining, structural support, and external skin—may require reconstruction with tissues harvested from distant sites through microvascular free tissue transfer. Our objective in this article is to discuss the general approach to nasal reconstruction and present the considerations for free tissue transfer with regard to each nasal component. The virtues of free flap transfer as well as its shortcomings and potential complications are discussed.
Keywords: nose; rhinectomy; reconstruction; microvascular flap